2010
DOI: 10.1177/0891241610377199
|View full text |Cite
|
Sign up to set email alerts
|

Disputes and Going Concerns in an Institution for “Troublesome” Boys

Abstract: Everett C. Hughes's classic concept of a "going concern" should stand for both entire institutions and for chains of activities within institutions. In this article the author explores this expanded version of Hughes's concept to show how staff and residents in a youth care setting interweave everyday concerns-meals, lessons, breaks, meetings, or other mundane but concerted projects-with interpersonal disputes. The author thereby offers a more nuanced understanding of how antagonist actors in institutions invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 13 publications
(22 reference statements)
0
35
0
1
Order By: Relevance
“…Wästerfors, 2011). Highlighting the intricacies of social control work, Wästerfors (2011) found that staff responses to "interpersonal troubles" or disputes with detained boys at a Swedish detention home were quite varied (thus, not only in line with, for example, the token economy that was in use). Staff members attempted to protect the activity at hand (for example, a music lesson) and prevent a dispute from interrupting it, but also used the activity as a means of ending the dispute.…”
Section: Staff Identitiesmentioning
confidence: 93%
See 4 more Smart Citations
“…Wästerfors, 2011). Highlighting the intricacies of social control work, Wästerfors (2011) found that staff responses to "interpersonal troubles" or disputes with detained boys at a Swedish detention home were quite varied (thus, not only in line with, for example, the token economy that was in use). Staff members attempted to protect the activity at hand (for example, a music lesson) and prevent a dispute from interrupting it, but also used the activity as a means of ending the dispute.…”
Section: Staff Identitiesmentioning
confidence: 93%
“…From a different perspective, ethnographers like Kivett and Warren (2002) and Wästerfors (2009bWästerfors ( , 2011 further complicate the picture of detention homes as total institutions with monolithic control over their inmates, illuminating how power or social control is not fully pervasive, but rather how it emerges as a micro-political and bidirectional phenomenon. Kivett and Warren (2002) document "the micro-politics of trouble" at a detention home in the United States that appears to embody the disciplinary gaze of a total institution, specifically through the use of a behavior modification program: token economy (TE).…”
Section: Ethnographies Of Youth Detention Homesmentioning
confidence: 99%
See 3 more Smart Citations